Kesulitan Belajar, Tantangan, dan Solusi Bagi Peserta Didik - Fandi Kurniawan; Nurhalisa, Nia; Ma’mun Hanif (STAI AL-AMIN, 2025)
Complex conditions known as learning difficulties can make it challenging for students to effectively learn, retain, and apply information. These difficulties frequently cause a discrepancy between a student's actual academic achievement and their intellectual potential. The purpose of this study is to investigate the definition, types, causes, and potential remedies for students' learning challenges. Using a literature review methodology, the study consults a number of pertinent scholarly sources. The results show that dyslexia, dysgraphia, and dyscalculia are common learning disabilities that can be caused by both external (family, school, and social) and internal (brain function disorders, genetic influences, and lack of interest or talent) factors. Identification, diagnosis, and prognosis are the first steps in addressing these issues. Tutoring and remedial education are then used to provide support and therapy. According to the study's findings, helping students realize their full potential requires a thorough grasp of the underlying causes and the application of suitable intervention techniques.